Analisis Peraturan Perundangan-Undangan/Kebijakan Profesi Keguruan - Najwatus Shifa; Iffah Maulida Alawiyyah; Puspo Nugroho (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
Legislative regulations apply from the term legislation which is defined as legislation and making laws, the term wetgeving is translated to mean forming laws, and the whole of state law, while the term Gesetzgebung is translated to mean legislation. This researcher aims to reveal various types of legislation/policies for the teaching profession. This research is qualitative research with data mining techniques using literature study. The data analysis went through three stages: data reduction, presentation, and drawing conclusions. The results of this research show that there are several kinds of laws and regulations/policies for the teaching profession, including: Law on Teachers and Lecturers, Law No. 20 of PP RI No. 19 of 2005, PP RI No. .74 in 2008.